ICESat-derived lithospheric flexure as caused by an endorheic lake's expansion on the Tibetan Plateau and the comparison to modeled flexural responses. (15th October 2017) - Madson, Austin; Sheng, Yongwei; Song, Chunqiao
Graphical abstract: Highlights: Lake-adjacent lithospheric deflection rates are derived from ICESat GLAS data. Elastic lithospheric response to short-term GLAS derived load fluxes are modeled. Responses to long-term optical/RADAR altimeter derived load fluxes are modeled. The measured lithospheric deflection cannot be explained by modeled elastic response. Abstract: A substantial and rapid expansion beginning in the late 1990s of Siling Co, the largest endorheic lake on the central Tibetan Plateau (TP), has caused a measurable lithospheric deflection in the region adjacent to the lake. Current broad-scale measuring of this flexural response is mainly derived from InSAR processing techniques or time-consuming field campaigns. The rheological constraints of the lithosphere from the underlying lithospheric response to large lake loads in this region are not well understood. This paper highlights a more efficient spaceborne LiDAR remote sensing technique to measure the deflection in the vicinity of Siling Co and to investigate the mechanisms of the observed lithospheric response in order to garner a better understanding of the local rheology. A lake-adjacent deflection rate and Siling Co water load variations are calculated utilizing the Geoscience Laser Altimeter System (GLAS) onboard NASA's Ice, Cloud and land Elevation Satellite (ICESat) and the joint NASA/USGS Landsat series of Earth observing satellites. A downward deflection rate of ∼5.6 mm/yr for the first 4 km of lake-adjacent land is calculated from the GLAS instrument, and this response is compared to the flexural outputs from a spherically symmetric, non-rotating, elastic, and isotropic (SNREI) Earth model in order to better understand the underlying mechanisms of the lithospheric response to the rapid increase of Siling Co loads. The modeled elastic response is ∼6.9 times lower than the GLAS derived flexure, thereby providing further evidence that a purely elastic lithospheric response cannot explain the deflection in this region. The relationship between the modeled elastic response and the GLAS derived flexure is applied to a long-term lake load change dataset to create the longest-running flexural response curve as caused by the last ∼40 years of Siling Co load variations, and these results show an accumulated lake-adjacent flexure of ∼12.6 cm from an overall lake load increase of 25.9 Gt. Our findings help to provide a better understanding of the lithospheric response to the recent expansion of Siling Co by introducing a new spaceborne laser altimeter derived technique to measure surface deformation caused by an extreme case of hydrologic loading.